Joint energy and shot mechanical energy of glide-style shot put - Chen, C.-F.; Chuang, M.-H.; Wu, H.-J. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2025)
Shot put is a throwing exercise in track and field. Performance has a strong relationship with the thrower`s height, technique, and energy transferred. The purpose of this study was to compare basic kinematics, joint movement, shot mechanical energy, and joint energy of the male glide-style shot put between high-performance (HP) and low-performance (LP) athletes. Data for 12 right-handed male shot putters with glide-style was captured at the National Games held in Taipei city in 2013. The HP (n = 6) and LP (n = 6) groups were classified according to their best throwing distance in the competition. Additionally, the 2D kinematics of their joints and shots were obtained by Kwon 3D motion analysis. Finally, the kinematics and energy were calculated in Excel software package. Results showed significant differences in throwing distance, the relationship between throwing distance and body height index (RDH index), release velocity, and the shoulder-shot (BSX) angle at right toe-off ground instant (RTF) and the angle difference between the right toe-off instant and release instant (RI-RTF) between the HP and LP groups. However, the energy of the joints and shots were not significantly different between the two groups. The better throwers exhibited a faster release velocity, accompanied by a smaller change in the SSX angle, and the SSX angle can be used by the coach to assess the body`s forward or backward tilt during training.